2001
DOI: 10.1002/1521-396x(200106)185:2<357::aid-pssa357>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Solution Strengthening by Oxygen in Nb-Ta and Nb-Mo Single Crystals

Abstract: We have investigated the high-temperature solid-solution strengthening by oxygen in Nb, Nb-Ta and Nb-Mo single crystals by compression tests with constant strain rate. Nb, Nb-20Ta, Nb-40Ta, Nb-20Mo, and Nb-40Mo single crystals with various O content were grown by use of the electron-beam floating zone melting method. It is found that Nb and Nb-Ta single crystals are strengthened by oxygen at temperatures below 1100 K, while Nb-20Mo single crystals are strengthened even at 1473 K. The critical resolved shear st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Unfortunately, as far as we have surveyed, reasonable activation energy values for the impurity diffusion of Si and Ti in Mo have not yet been reported. For the activation energy of creep in Mo-Si-B-based alloys, more careful discussion of impurity diffusion and interstitial (I)-substitutional (S) impurity interaction effects may be needed 35 , 36 . Most of the authors listed in Table 3 reported stress exponents between 3 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, as far as we have surveyed, reasonable activation energy values for the impurity diffusion of Si and Ti in Mo have not yet been reported. For the activation energy of creep in Mo-Si-B-based alloys, more careful discussion of impurity diffusion and interstitial (I)-substitutional (S) impurity interaction effects may be needed 35 , 36 . Most of the authors listed in Table 3 reported stress exponents between 3 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…ii) The solute O atoms may interact with screw and edge dislocations and impede the dislocation motion [21].…”
Section: Discussionmentioning
confidence: 99%
“…Loomis and Gerber 54) reported that CRSS of Nb single crystal increases linearly wih O+N+C concentration up to 0.2 mol% with a hardening rate of 170 MPa/mol%(O+N+C). Miura et al 55) showed that CRSS of Nb-4.55 mol%O is 600 MPa with the average hardening rate of 130 MPa/ mol%O, while in Nb-20Ta-O single crystals CRSS increases linearly with oxygen concentration with a rate of 240 MPa/ mol%O. The present result of the average hardening rate of 175 MPa/mol%O seems consistent with the above results.…”
Section: Strengthening Mechanisms Of Gum Metal At Room Temperaturementioning
confidence: 99%